1999
DOI: 10.1093/humrep/14.8.2020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone as a seminal marker for spermatogenesis in non-obstructive azoospermia

Abstract: Anti-Müllerian hormone (AMH) also known as Müllerian inhibiting substance or factor, is a Sertoli cell-secreted glycoprotein responsible in male embryos for Müllerian duct regression. However, its role in adults remains unknown. AMH seminal concentrations have been evaluated using an enzyme-linked immunoassay in three groups of young men: group 1, fertile donors (n = 18); group 2, obstructive azoospermia (n = 9) after vasectomy or associated with deferent duct agenesia; and group 3, non-obstructive azoospermia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
13

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 21 publications
1
40
0
13
Order By: Relevance
“…Seminal plasma AMH has been proposed as a noninvasive marker of persistent hypospermatogenesis in cases of nonobstructive azoospermia (24) or oligoasthenoteratozoospermia (31) because the hormone is secreted predominantly into the seminiferous tubules; nevertheless, its use was not widely adopted, possibly as a result of concerns that the presence of seminal proteases could influence AMH levels in the seminal plasma. In two recent studies, no differences were detected in serum (25) or seminal (26) AMH levels between men with azoospermia with or without spermatozoa during a TESE procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal plasma AMH has been proposed as a noninvasive marker of persistent hypospermatogenesis in cases of nonobstructive azoospermia (24) or oligoasthenoteratozoospermia (31) because the hormone is secreted predominantly into the seminiferous tubules; nevertheless, its use was not widely adopted, possibly as a result of concerns that the presence of seminal proteases could influence AMH levels in the seminal plasma. In two recent studies, no differences were detected in serum (25) or seminal (26) AMH levels between men with azoospermia with or without spermatozoa during a TESE procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After manual searching of the results, we located 15 studies for INHB (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and three studies for AMH (24)(25)(26) that directly examined the role of these hormones as predictors of sperm retrieval during a testicular biopsy in men with azoospermia. Nevertheless, in none of these studies was there any report on the combined predictive value of serum INHB and AMH levels.…”
mentioning
confidence: 99%
“…Serum inhibin B was claimed to be positively related to sperm retrieval on testicular sperm extraction, and to distinguish UOA from OA [25], but these data were not confirmed [26]. Nitric oxide [2,4], transferrin and its soluble receptors [27], and anti-Müllerian hormone [28] have been proposed as markers of spermatogenesis, but the techniques lack sensitivity and especially specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in AMH and ADCYAP1R1 in newborn males reflects the maturation status of Sertoli cells (Rey et al, 1993;Koh and Won, 2006;Boukari et al, 2009). Another study reported that the loss of AMH was associated with non-obstructive azoospermia (Fenichel et al, 1999). RHOX5 is an androgen-dependent protein, which regulates spermatogenesis (Domanskyi et al, 2007;Hu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…RHOX5 is an androgen-dependent protein, which regulates spermatogenesis (Domanskyi et al, 2007;Hu et al, 2007). Sertoli cells mediate spermatogenesis by nourishing the development of sperm cells, thus the expression levels of AMH, RHOX5, AD-CYAP1R1, and PDGFRA reflect the functions of Sertoli cells (Fenichel et al, 1999;Jamen et al, 2000;Basciani et al, 2002;Denolet et al, 2006). However, if ICSI affects spermatogenesis, why was the downregulation of Pdgfra followed by the increased expression of Rhox5?…”
Section: Discussionmentioning
confidence: 99%